Mitochondria in diseases: from cell power plants to DAMPs - Devulder, Justine (Thorax, 2023)
Advances in medicine and the improvement in controlling haemorrhages following trauma have dramatically increased the survival of many people. However, according to the WHO, trauma still accounts for 10% of deaths and 16% of disabilities worldwide—considerably more than infectious diseases, including malaria, tuberculosis and HIV.1 Indeed, once bleeding has stopped, some patients develop multiorgan failure often accompanied by systemic inflammatory response syndrome (SIRS).2 SIRS can be triggered by the inflammatory response to blood loss and tissue damage rather than an infection. In that case, SIRS is called sterile sepsis and is thought to be induced by the release of endogenous molecules called damage-associated molecular patterns (DAMPs) from the site of tissue injury by inflammatory cells, including neutrophils and necrotic cells.2 Among DAMPs, mitochondria and mtDNA have generated scientific interest as they provoke a vigorous response and seem to trigger severe illnesses in humans, including SIRS. In their Thorax paper, Tiwari-Heckler et al have developed an elegant study to understand how this essential organelle participates in the immune response observed during SIRS.3